Triggering TLR2, -3, -4, -5, and -8 Reinforces the Restrictive Nature of M1- and M2-Polarized Macrophages to HIV - Schlaepfer, Erika (American Society for Microbiology, 2014)
Macrophages must react to a large number of pathogens and their effects. In chronic HIV infection, the microenvironment changes with an influx of microbial products that trigger Toll-like receptors (TLRs). That dynamic nature can be replicated ex vivo by the proinflammatory (M1-polarized) and alternatively activated (M2-polarized) macrophages. Thus, we determined how polarized macrophages primed by various TLR agonists support HIV replication. Triggering of TLR2, -3, -4, -5, and -8 reinforced the low level of permissiveness in polarized macrophages. HIV was inhibited even more in M1-polarized macrophages than in macrophages activated only by TLR agonists. HIV was inhibited before its integration into the host chromosome. Polarization and triggering by various TLR agonists resulted in distinct cytokine profiles, endocytic activity, and distinct upregulation of restriction factors of HIV. Thus, different mechanisms likely contribute to the HIV-inhibitory effects. In chronic HIV infection, macrophages might become less permissive to HIV due to changes in the microenvironment. The high level of reactivity of polarized macrophages to TLR triggering may be exploited for immunotherapeutic strategies. IMPORTANCE Macrophages are a major target of HIV-1 infection. Different cell types in this very heterogeneous cell population respond differently to stimuli. In vitro, the heterogeneity is mimicked by their polarization into proinflammatory and alternatively activated macrophages. Here we explored the extent to which agonists triggering the TLR family affect HIV replication in polarized macrophages. We found that a number of TLR agonists blocked HIV replication substantially when given before infection. We also report the mechanisms of how TLR agonists exert their inhibitory action. Our findings may advance our understanding of which and how TLR agonists block HIV infection in polarized macrophages and may facilitate the design of novel immunotherapeutic approaches.